(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The article reveals the essence, basic requirements and organizational and methodological aspects of assessing the creditworthiness of commercial bank customers. Proposals have been developed to theoretically and organizationally and methodologically improve the creditworthiness of the bank’s customers.